Implications of Multiculturalism and Tolerance in Islamic Religious Education - Muh Barid Nizarudin Wajdi; Tobroni Tobroni (EDUCATIO : Journal of Education, 2020)
Education aims to shape attitudes and behaviors towards civilized human beings. An education system that only emphasizes the transfer of knowledge, makes education no longer meaningful and has a positive effect on learners. It is less touching on the humanism side that ultimately develops pluralism as the foundation of multiculturalism. This model of religious education will only create learners to make "abdullah" that is only pious individually. The understanding of pluralism and multiculturalism that has become a commodity in the political field will continue to roll in the realm of national education, including Islamic religious education which is integrally part of the national education system. The purpose of this research is to illustrate the implementation and implications of multicultural-based PAI at SMA Kertosono. This research uses qualitative approach with case study type. The results showed that the implementation of multicultural-minded Islamic religious education (PAI) at SMA Negeri Kertosono,was carried out through 2 stages, namely: a) Learning activities in the classroom, through: (1) Morning prayer together; (2) To give all students the opportunity to receive religious lessons according to their beliefs; (3) Be universal and discriminate against students; (4) Giving accuracy; (5) Uphold respect and respect; b)Implementation of multicultural-minded PAI in school activities outside the classroom, through: a) Religious extracurricular activities carried out during islamic activities and commemorations, as well as Friday prayers and Femininity; b) Activities of a social nature. 2) The impact of the implementation of Islamic religious education (PAI) multicultural-minded in building religious tolerance in SMA Negeri Kertosono, among others: a) The creation of a comfortable and conducive learning atmosphere; b) School activities run smoothly and have a high tolerance ;c) The realization of religious harmony and harmony in differences; d) Avoid conflict and division; e) The creation of a culture of mutual respect, respect and accepting of differences